Resistance to Marginalization in America as Reflected in Kathryn Stockett's 'The Help' - Normalisa, Devita; Rosyidi, Mohamad Ikhwan (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
Slavery and racial segregation are two important events that shaped American history. Although slavery had been abolished constitutionally by the Thirteenth Amendment, racial segregation remained existing in some southern states of the US until Civil Rights Movement in 1960s. Racial segregation in the US was regulated by Jim Crow laws which promoted Ã¢â‚¬Å“separate but equalÃ¢â‚¬Â rules. This situation is reflected in Kathryn StockettÃ¢â‚¬â„¢s novel entitled The Help which mostly portrays the life of black maids under Jim Crow laws in Jackson, Mississippi during 1960s. This study aims to find the resistance to marginalization that is caused by racial discrimination, as well as the factors that underlies the resistance. The method of this study is a qualitative study. The data is analyzed by GramsciÃ¢â‚¬â„¢s hegemony theory and scooped by sociology of literature. Then, the method of data analysis is based on the conflicts of characters in the novel; white and black characters. The Help shows that marginalization of African Americans is created from the opposition that occur because of racial hegemony; the ruling class and the ruled class, the controlling and the controlled, the free ones and the restricted ones, the strong ones and the weak ones, or the voiced ones and the silenced ones. The Help also shows that the resistance to marginalization can be done by producing literature. The resistance of the African Americans happens as a result of oppression and inhumane treatment. It also happens as a result of black peopleÃ¢â‚¬â„¢s consciousness that sees racial discrimination as a system that is full of flaws. Keywords: hegemony, marginalization, racial discrimination, resistance